Bystanders’ cardiopulmonary resuscitation involvement in the treatment of out-of-hospital cardiac arrest events and educational status regarding basic life support measures and automated external defibrillator usage among residents in Canton Sarajevo, Bos - Adem Zalihić; Armin Šljivo; Emina Ribić; Aida Gavranović; Lejla Brigić (Medicinski glasnik, 2022)
Aim: To investigate bystanders’ CPR involvement in out-of-hospital cardiac arrest (OHCA) events, their current knowledge regarding OHCA and BLS measures, their willingness to learn BLS measures with the usage of AEDs, as well as current practices. Methods: This cross-sectional study included: data regarding all OHCA events treated at the Emergency Medical Service of Canton Sarajevo between January 2015 and December 2019, and an online anonymous questionnaire that examined knowledge, attitudes and practices regarding basic life support (BLS) and automated external defibrillators (AEDs). Results: A total of 328 (24.0 %) of 1362 OHCA events achieved the return of spontaneous circulation (ROSC). OHCA incidence was 62/100.000 inhabitants per year. Male gender (p=0.043) and younger age (p<0.001) were significantly associated with obtaining ROSC. Only 44 (3.2%) OHCA events were assisted by bystanders, who were mostly medical professionals 38 (86.4%), followed by close family members 6 (13.6%). There was no report of AED usage. BLS and AED knowledge test score was in the range 12.0-89.8% with generally poor knowledge. Our residents agreed that BLS measurements are essential, 1604 (86.7 %) and that BLS should be a part of their curriculum, 1678 (90.7 %). Conclusion: The prevalence of OHCA events in Bosnia and Herzegovina is similar to the region; ROSC among OHCA events was lower than European average, but among highest in the region. There was an extremely low rate of bystander engagement and no AEDs usage. Governmental institutions and health agencies should intervene to increase population knowledge thus increasing OHCA survival rate.
Keywords: CPR; heart arrest; out-of-hospital cardiac arrest; return of spontaneous circulation